Service quality evaluation for urban rail transfer facilities with Rasch analysis - Kim, Junghwa; Schmöcker, Jan Dirk; Yu, Jeong Whon; Choi, Jung Yoon (Travel Behaviour and Society, 2018)
This paper evaluates the service level of urban rail transfer facilities based on Rasch analysis, taking into account transit users’ subjective perceptions. A total of 3970 respondents who usually transfer between different urban rail lines at least 3 times a week and who are between 15 and 75 years old were randomly surveyed. We evaluate the transfer station service quality by capturing satisfaction with a range of service items. The items are grouped into five criteria: information, mobility, comfort, convenience and safety. The satisfaction with the five criteria is further distinguished based on trip purpose. From the results, it was concluded that service items related to transfer time (train arrival information, walking distance) are important to users during commute, educational, business and leisure trips. Instead important service items for transfer convenience when on shopping or leisure trips are walking amenity, waiting space, parking lot usability or specific facilities such as the presence of baby-care rooms. Considering also the characteristics of Seoul's transit network we discuss which transfer facilities are likely to be a key for encouraging people to use urban rail and suggest that Rasch analysis is a suitable tool for this type of evaluation that is not frequently used in transport planning.
Keywords: Level of service; Public transport; Rasch analysis; Service quality; Transfer